Distinct Role of TNFR1 and TNFR2 in Protective Immunity Against Orientia tsutsugamushi Infection in Mice - Liang, Yuejin; Fisher, James; Gonzales, Casey; Trent, Brandon; Card, Galen; Sun, Jiaren; Tumanov, Alexei V.; Soong, Lynn (Frontiers in Immunology, 2022)
Infection with Orientia tsutsugamushi, an obligate intracellular bacterium, can cause mild or severe scrub typhus. Some patients develop acute lung injury, multi-organ failure, and fatal infection; however, little is known regarding key immune mediators that mediate infection control or disease pathogenesis. Using murine models of scrub typhus, we demonstrated in this study the requirement of TNF-TNFR signaling in protective immunity against this infection. Mice lacking both TNF receptors (TNFR1 and TNFR2) were highly susceptible to O. tsutsugamushi infection, displaying significantly increased tissue bacterial burdens and succumbing to infection by day 9, while most wild-type mice survived through day 20. This increased susceptibility correlated with poor activation of cellular immunity in inflamed tissues. Flow cytometry of lung- and spleen-derived cells revealed profound deficiencies in total numbers and activation status of NK cells, neutrophils, and macrophages, as well as CD4 and CD8 T cells. To define the role of individual receptors in O. tsutsugamushi infection, we used mice lacking either TNFR1 or TNFR2. While deficiency in either receptor alone was sufficient to increase host susceptibility to the infection, TNFR1 and TNFR2 played a distinct role in cellular responses. TNF signaling through TNFR1 promoted inflammatory responses and effector T cell expansion, while TNFR2 signaling was associated with anti-inflammatory action and tissue homeostasis. Moreover, TNFRs played an intrinsic role in CD8+ T cell activation, revealing an indispensable role of TNF in protective immunity against O. tsutsugamushi infection.